Pengaruh Lingkungan Kerja Non Fisik, Work From Home dan Kompetensi Terhadap Produktivitas Kerja Pegawai Pada Kantor Dinas PUPR Provinsi Bengkulu - Oktaviani, Oktaviani (UNIB Press, 2024)
This study aims to examine and analyze the influence of the non-physical work environment, work from home, and competence on employee work productivity at the Bengkulu Provincial PUPR Service. The type of research used is descriptive quantitative with primary data obtained from offline questionnaires. The data collection technique used a questionnaire, with a sample of 163 people. The analytical method used is Multiple Linear Regression, t-test (partial), f-test (simultaneous) and determination (R2) with data processing tools using the SPSS For Windows Version 16.0 program. The results showed that all statement items for the variables in the research carried out were valid and reliable. In testing the hypothesis, the non-physical work environment (X1) has a positive and significant effect on employee work productivity. work from home (X2), has a positive and significant effect on employee work productivity. and competence (X3), have a positive and significant effect on employee work productivity. The F test shows that non-physical work environment, work from home and competence have a simultaneous effect on employee work productivity. Keyword: Work From Home; Competence; Non-Physical Work Environment; Work Productivity